Immersion Pulmonary Edema in Female Triathletes - Eric A. Carter; Michael S. Koehle (Pulmonary Medicine)
Pulmonary edema has been reported in SCUBA divers, apnea divers, and long-distance swimmers however, no instances of pulmonary edema in triathletes exist in the scientific literature. Pulmonary edema may cause seizures and loss of consciousness which in a water environment may become life threatening. This paper describes pulmonary edema in three female triathletes. Signs and symptoms including cough, fatigue, dyspnea, haemoptysis, and rales may occur within minutes of immersion. Contributing factors include hemodynamic changes due to water immersion, cold exposure, and exertion which elevate cardiac output, causing pulmonary capillary stress failure, resulting in extravasation of fluid into the airspace of the lung. Previous history is a major risk factor. Treatment involves immediate removal from immersion and in more serious cases, hospitalization, and oxygen administration. Immersion pulmonary edema is a critical environmental illness of which triathletes, race organizers, and medical staff, should be made aware.